2010
DOI: 10.1158/0008-5472.can-10-2177
|View full text |Cite|
|
Sign up to set email alerts
|

Gadd45a Functions as a Promoter or Suppressor of Breast Cancer Dependent on the Oncogenic Stress

Abstract: Gadd45a plays a pivotal role as a stress sensor that modulates cellular responses to various stress stimuli including oncogenic stress. We reported that the stress sensor Gadd45a gene functions as a tumor suppressor in Ras-driven breast tumorigenesis via increasing JNK-mediated apoptosis and p38-mediated senescence. In contrast, here, we show that Gadd45a promotes Myc-driven breast cancer by negatively regulating MMP10 via GSK3 b/b-catenin signaling, resulting in increased tumor vascularization and growth. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…We demonstrated that Gadd45a feeds into the Jnk-dependent signaling pathway to activate p53 when bcatenin is active. Consistent with this observation, Gadd45a deletion accelerates Ras-and Myc-driven mammary tumor formation, potentially through regulation of Jnk-induced apoptosis, 29,35 while MKK7-Jnk signaling pathway is required for activation of p53 in several mouse models of cancer. 30 It is important to note that Gadd45a deletion specifically affected b-catenin-induced activation but did not completely inactivate the Jnk-dependent signaling pathway.…”
Section: Discussionsupporting
confidence: 63%
“…We demonstrated that Gadd45a feeds into the Jnk-dependent signaling pathway to activate p53 when bcatenin is active. Consistent with this observation, Gadd45a deletion accelerates Ras-and Myc-driven mammary tumor formation, potentially through regulation of Jnk-induced apoptosis, 29,35 while MKK7-Jnk signaling pathway is required for activation of p53 in several mouse models of cancer. 30 It is important to note that Gadd45a deletion specifically affected b-catenin-induced activation but did not completely inactivate the Jnk-dependent signaling pathway.…”
Section: Discussionsupporting
confidence: 63%
“…The roles of GADD45a, PTPRV, PML, and CAV1 have been examined individually through the generation of knockout mice but none of these animals spontaneously develop cancer (Hollander et al 1999;Razani et al 2001;Rego et al 2001;Doumont et al 2005). However, similar to other candidate TP53 tumor-suppressor transcriptional targets, their deficiency can accelerate tumor formation under conditions of specific oncogenic stress (Capozza et al 2003;Tront et al 2010).…”
Section: Cell-cycle Regulation and Dnadamage Repairmentioning
confidence: 99%
“…GADD45A has been reported to have the dual and seemingly conflicting functions of tumor promotion and tumor suppression with the outcome being highly dependent on the oncogenic stimuli. 52 Moderate DNA damage can trigger GADD45A to exert an antiapoptotic function, binding to other proteins to enhance DNA repair, whereas excessive DNA damage may act as a prompt for apoptosis, possibly acting as a survival mechanism during situations where irreparable cell damage is evident. 53 FLT3LG is a critical transmembrane protein well documented to stimulate the proliferation of hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%